Avaliação microestrutural de cascas cerâmicas utilizadas na produção de moldes para o processo de fundição por cera perdida - Iona Macedo Leonardo Machado (2005)
Parts having excellent surface finishing and low dimensional tolerances characterize the lost wax process. These characteristics are caused by wax properties of copying details and reproducing the details by ceramic shells. Therefore it is very important to know the relation among processing, microstructure and properties of ceramic shells. It was studied the microstructure of ceramic shell, determining density and porosity parameters, using mercury pycnometry, helium pycnometry, water absorption test, scanning electron microscopy and bending tests. Test pieces of ceramic shell with five different layers were fabricated. A ceramic shell with polymer was tested for comparison. Relations among processing, microstructure and properties of ceramic shells were analysed. Some expectations related to ceramic shells have been observed, like: - Modulus of rupture after sintering is higher than the modulus of rupture of the green body; Modulus of rupture tends to decrease when polymer percentages increase; Layer bending strength decreases when the grain size of stuccoing increases. The average modulus of rupture of the layers is similar to the respective ceramic shell modulus of rupture. When polymer was used, the open porosity of sintered ceramic shell was higher than the open porosity of green ceramic shell. Helium and mercury pycnometries have shown efficient techniques in the evaluation of ceramic shell densities and layers densities, with good accuracy. Values of water absorption densities were found between helium and mercury pycnometries results. Electron scanning microscopy results showed the complexity of the ceramic shell microstructure, and it was possible to observe the difference of microstructure among different processing conditions